PENINGKATAN KOMPETENSI GURU MELALUI EDUKASI DAN PENDAMPINGAN PENGEMBANGAN MEDIA AJAR BERBASIS ARTIFICIAL INTELLIGENCE - Musdar M; Ahmad Junaedi (Universitas Mataram, 2025)
Teaching media serve as one of the tools or methods used in the teaching and learning process. They function not only as aids for teachers in delivering material but also as means to enhance students’ active engagement, accommodate diverse learning styles, and create an enjoyable and interactive learning environment. Artificial Intelligence (AI) technology has developed rapidly and is increasingly being applied in the field of education, including in the development of instructional media. The purpose of this activity is to improve teachers’ competence in developing instructional media by utilizing AI technology. The method used was a participatory approach, aimed at enabling partners to be actively involved in every stage of the activity through training sessions and hands-on practice in developing AI-based teaching materials. The program facilitated practical sessions for creating instructional media, along with mentoring and technical guidance to help participants refine and further develop their teaching materials. Teachers’ competence in developing AI-based instructional materials was measured using a Likert scale (1–5) survey administered before and after the training. The results showed a significant improvement in teachers’ competence, with the percentage of those who “understood” increasing from 40% to 93.33% in the “highly understood” category. This represents a 53.33% increase in teacher competence, indicating that teachers have developed strong skills in utilizing AI-based instructional media and have gained greater awareness of the importance of enhancing their technological competence to improve the quality of learning. Keywords: Education; Guidance; Competence; Instructional Media; Artificial Intelligence.